Fiscal reaction function and fiscal fatigue: Evidence for the euro area - Cristina Checherita-Westphal; Václav Žďárek (European Central Bank (ECB), 2017)
This paper estimates a fiscal reaction function (FRF) framework for euro area countries and derives a novel approach to measure fiscal fatigue. As in previous studies, we find evidence that euro area sovereigns abide, on average, by (weak) sustainability constraints. The primary balance improves by about 0.03-0.05 for every 1 percentage point increase in the debt-to-GDP ratio after controlling for other relevant factors. The positive reaction of primary surpluses to higher debt strengthened over the crisis. Based on this framework, we propose a simple, practical measure of fiscal fatigue that can be used to assess the capacity of sovereigns to maintain primary surpluses over extended periods of time. This measure can be derived by comparing simulated primary balance paths in the context of debt sustainability analyses with countries' track-record, adjusted for the change in debt with the estimated fiscal reaction coefficient. The evidence of fiscal fatigue in non-linear FRF specifications is weaker for our euro area sample.
Keywords: H60; E62; F41; C33; 330; fiscal fatigue; fiscal reaction function; financial crisis; debt sustainability; euro area